The end of the world as we know it [large type] : new tales of Stephen King's The stand - Golden, Christopher; Golden, Christopher; Keene, Brian; Keene, Brian (Thorndike Press large print high octane., 2025)
"Since its initial publication in 1978, The Stand has been considered Stephen King's seminal masterpiece of apocalyptic fiction. Now, bringing together some of today's greatest and most visionary writers, The End of the World As We Know It features unforgettable, all-new stories set during and after the events of The Stand--brilliant, terrifying and painfully human tales that will resonate with readers everywhere as an essential companion to the classic, bestselling novel"--